Early Japanese Hossō in Relation to Silla Yogācāra in Disputes between Nara’s Northern and Southern Temple Traditions - Green, Ronald S. (Journal of Korean religions, 2020)
This paper examines the influence of writings by Silla Yogācāra Buddhists on the formation of orthodox interpretations within the Hossō tradition, Japanese Yogācāra. Part One considers the frequency of citations of Silla masters and their texts in principal Hossō writings and suggests several implications of this. Some of the Silla writings used by Hossō thinkers in support of their views were specifically condemned by the Chinese Faxiang tradition. This contradicts descriptions by Gyōnen and other historians of Hossō as an imported copy of Faxiang. Part Two of the article assesses four points of argument between the Nara Hossō Northern Temple (Kōfukuji) tradition and Nara Hossō Southern Temple (Gangōji) tradition. It is shown that these disputes persisted for centuries in Japanese Yogācāra and that the two traditions used Silla interpretations in opposing ways. Many prominent Hossō authorities relied on Silla texts that challenge Faxiang understandings of epistemology, ontology, and logic.